Social Dominance in Saudi Narration, Sociological Approach in selected novels - Althumairi, Shoroq Abdullah (Journal of Humanities & Social Sciences, 2025)
The concept of social dominance is linked to the structuring of social relationships, where certain groups prevail over others through influence and control, whether this control is economic or intellectual. Dominance refers to the ability of a particular group or social class to impose its influence, values, and ideology on society as a whole, leading to the formation of unequal power relationships among different groups. This dominance relies on soft power, such as ideology and culture, in addition to economic power. Social dominance is a critical factor in shaping social relationships, and literature plays an important role in highlighting social and cultural issues. Representations of social dominance are a central theme in many novels, allowing authors to explore relationships between different classes and groups within society, as well as to depict patterns of control and conflict.